2018
DOI: 10.1007/s10802-018-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Depression and Substance Use: the Protective Role of Prosocial Peer Behavior

Abstract: Adolescents with depression disorders have higher rates of substance use. In order to advance contextually relevant mental health interventions, basic research is needed to test social ecological mechanisms hypothesized to influence adolescent depression and substance use. Accordingly, we conducted growth curve modeling with a sample of 248 urban adolescents to determine if depression's effect on substance use was dependent upon peer network health (sum of peer risk and protective behaviors) and activity space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
(46 reference statements)
1
27
0
Order By: Relevance
“…For example, an empirical study of 500 pairs of twins showed that the genetic influence on rule-breaking behavior was several times greater in those with low-level PPA than in those with high-level PPA (Burt and Klump, 2014). Moreover, other research has shown that prosocial peer network moderated the effects of depression on substance use (Mason et al, 2019). Therefore, it is reasonable to expect that PPA can moderate the direct and indirect link between cybervictimization and adolescents' IA.…”
Section: The Moderating Role Of Prosocial Peer Affiliationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an empirical study of 500 pairs of twins showed that the genetic influence on rule-breaking behavior was several times greater in those with low-level PPA than in those with high-level PPA (Burt and Klump, 2014). Moreover, other research has shown that prosocial peer network moderated the effects of depression on substance use (Mason et al, 2019). Therefore, it is reasonable to expect that PPA can moderate the direct and indirect link between cybervictimization and adolescents' IA.…”
Section: The Moderating Role Of Prosocial Peer Affiliationmentioning
confidence: 99%
“…Consistent with this theory, many empirical studies indicate that adolescents with a high proportion of prosocial peers are less likely to engage in substance use and delinquency ( Barry and Wentzel, 2006 ; Han and Margolin, 2016 ). More importantly, research has also shown that PPA can significantly buffer personal and environmental risk factors on adolescents’ academic, emotional, and behavioral adjustment ( Burt and Klump, 2014 ; Han and Margolin, 2016 ; Mason et al, 2019 ). For example, an empirical study of 500 pairs of twins showed that the genetic influence on rule-breaking behavior was several times greater in those with low-level PPA than in those with high-level PPA ( Burt and Klump, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prosocial behavior can reduce college students’ depressive symptoms and improve their interpersonal relationships, subjective well-being, and life satisfaction ( Davis et al, 2016 ; Mason et al, 2019 ). The present study demonstrated that different components of empathy (perspective-taking, fantasy, empathic concern, and personal distress) have different impacts on prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Much remains to be learned about the role of peer relationships in this process. It is possible, for example, that depressed adolescents select peers who use drugs and alcohol (Siennick et al, 2016), or that depressed peers model the use of drugs and alcohol as self‐medication for symptoms of depression (Mason et al, 2019). The present findings highlight a small part of the picture, but future research should take a developmental systems perspective, positioning mental health and substance use within family, peer and neighbourhood systems.…”
Section: Discussionmentioning
confidence: 99%